Understanding Social Practices Within Public Health Research: Developing an Innovative, Integrative and Qualitative ‘Methods Menu’ - Caitlan McLean; Linda Slack-Smith; Paul R. Ward (International Journal of Qualitative Methods)
Social practice theory offers valuable insights for public health research, particularly in understanding how health inequalities are sustained through everyday practices. A recent increase in social practice theory scholarship has focused on the development of flexible methodologies which allow for empirical investigations of social practices. This paper introduces a flexible, practice-based approach designed to address methodological challenges in studying interconnected practices, which we call a “method menu”. The method menu allows for the adaptable selection of data collection methods, including practice-based interviews, observations of practice spaces, and explorations of material and digital elements. The approach we outline also allows flexibility for the participants, by offering choice and control over engagement within the data collection process, with considerations of their preferences, availability and consent. Using a metaphorical menu structure, participants can engage in the research project and choose to commit to only a single interview or commit to multiple courses of data collection (i.e. interviews and home visit). The method menu facilitates modification of participation over time to address barriers to research participation. The method menu was developed and tested through research examining early childhood oral health practices within naturally living families. Developed using a social practice theory perspective, it facilitates the investigation of both individual performance of practices and their relational dynamics, particularly in contexts where traditional ethnographic methods or prolonged investigations may be constrained. Even where traditional ethnographic approaches are feasible, the method menu can offer researchers a way to undertake data collection that grants participants greater agency in determining their level of research engagement. The method menu responds to calls for methodological innovation within SPT research while acknowledging the complexities researchers may encounter within broader research fields.